1998
DOI: 10.1046/j.1365-2869.1998.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

A dose–response study of total sleep time and the ability to maintain wakefulness

Abstract: SUMMARYThe apparent connection between sleep debt, performance decrements and workplace accidents has generated a need for feasible vigilance tests that focus on the quantification of daytime sleepiness in occupational settings. The objective of this study was to evaluate the sensitivity of the Maintenance of Wakefulness Test (MWT) to acute sleep deprivation of various doses. Eight healthy female volunteers, mean age 28.9 years (range 23-36), participated in this laboratory study. After an adaptation night, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
24
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 2 publications
5
24
1
Order By: Relevance
“…For sleep disorders, our finding confirms the results of some investigations which concerned truck drivers 16,18,19,33) and construction workers 34) . Sleep disorders act on fatigue, vigilance, ability in assessing or watching the work environment and work conditions 18) .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For sleep disorders, our finding confirms the results of some investigations which concerned truck drivers 16,18,19,33) and construction workers 34) . Sleep disorders act on fatigue, vigilance, ability in assessing or watching the work environment and work conditions 18) .…”
Section: Discussionsupporting
confidence: 89%
“…Sleep disorders act on fatigue, vigilance, ability in assessing or watching the work environment and work conditions 18) . As expected, requesting a job change also played a role in occupational injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the experience and job knowledge cannot eliminate the injuries if the number of demanding hazards is continuously high. Thus, prevention should focus especially on those hazards that affect working capacity of the workers and consequently the quality of task performed, alertness, vigilance, and observing numerous hazards [3,33]. Our studies found that, like occupational factors, the personal ones such as regular alcohol use, sleep disorders, altered health status, frequent psychotropic drug use, and chronic diseases (especially musculoskeletal disorders), as well as physical, seeing, hearing, and cognitive disabilities, which may affect working capacity of the workers, also played a role in the injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, certain individual factors which concern many employed people such as young age [7][8][9][10][11] , body weight 12,13) , lack of training 14) , lack of experience 9,15) , smoking 14,[16][17][18][19] , alcoholic drink consumption 18,20) , sleep disorders 11,13,[21][22][23][24][25][26] , and some disabilities 27) , have been identified as risk factors for occupational injuries. Although prevention measures are mainly concerned with the work conditions, the knowledge of jobs at risk and the related risk factors could help occupational physicians to make workers, who are exposed to higher risk, more sensitive to the injury risks during the yearly medical examination.…”
mentioning
confidence: 99%